Modifiable risk factors for multidrug‐resistant Gram‐negative infection in critically ill burn patients: a systematic review and meta‐analysis. Issue 10 (3rd September 2019) - Vickers, Mark L.; Malacova, Eva; Milinovich, Gabriel J.; Harris, Patrick; Eriksson, Lars; Dulhunty, Joel M.; Cotta, Menino O.
Abstract: Background: We conducted a systematic review and meta‐analysis to identify potentially modifiable risk factors for multidrug‐resistant Gram‐negative colonization or infection in critically ill burn patients. Methods: A systematic search was conducted of PubMed, Embase, CINAHL, Web of Science and Central (Cochrane). Risk factors including antibiotic use and hospital interventions were summarized in a random‐effects meta‐analysis. Risk of publication bias was assessed using the Grading of Recommendations Assessment, Development and Evaluation method and funnel plots. Results: A total of 11 studies met the inclusion criteria. We identified several potentially modifiable risk factors and were able to grade their importance based on effect size. Related to prior antibiotic exposure, extended‐spectrum cephalosporins (pooled odds ratio (OR) 7.00, 95% confidence interval (CI) 2.77–17.67), carbapenems (pooled OR 6.65, 95% CI 3.49–12.69), anti‐pseudomonal penicillins (pooled OR 4.23, 95% CI 1.23–14.61) and aminoglycosides (pooled OR 4.20, 95% CI 2.10–8.39) were most significant. Related to hospital intervention, urinary catheters (pooled OR 11.76, 95% CI 5.03–27.51), arterial catheters (pooled OR 8.99, 95% CI 3.84–21.04), mechanical ventilation (pooled OR 5.49, 95% CI 2.59–11.63), central venous catheters (pooled OR 4.26, 95% CI 1.03–17.59), transfusion or blood product administration (pooled OR 4.19, 95% CI 1.48–11.89) and hydrotherapy (pooled OR 3.29, 95% CI 1.64–6.63) were most significant. Conclusion: Prior exposure to extended‐spectrum cephalosporins and carbapenems, as well as the use of urinary catheters and arterial catheters pose the greatest threat for infection or colonization with multidrug‐resistant Gram‐negative organisms in the critically ill burn patient population. Abstract : We conducted a meta‐analysis combining data from 11 studies to identify modifiable risk factors for multidrug‐resistant Gram‐negative infection in a burn intensive care unit. Risk factors included antibiotic exposures and hospital interventions. Cephalosporins and carbapenems posed the highest antibiotic risks while urinary and arterial catheters posed the highest hospital intervention risks.